Salud sexual reproductiva en estudiantes universitarios: conocimientos y prácticas - Ivett Adriana Herrera Zuleta; Jonathan Fernando Reyes Salazar; Katherine Patricia Rojas Velasco; Magda Lizeth Tipán; Carlos Andrés Torres López; Lina Marcela Vallejo Trujillo; Luis Felipe Zemanate Ordoñez (Universidad Francisco de Paula Santander, 2018)
Objective: To describe the knowledge and practices related to Sexual and Reproductive Health in the students of a University of the Suroccidente Colombiano. Materials and methods: Quantitative descriptive prospective cross-sectional study; was carried out in students enrolled in I and II semester in the fi rst academic period 2016; the calculation of the sample was obtained using the formula of unknown variance and known total population (3,489), obtaining a sample size of 415 students. A structured survey-type instrument was developed based on the counseling format of the university's sexual and reproductive health program. Data were processed through Excel and the SPSS version 22 statistical package, to determine the significance of the association was used Chi square test with a reliability of 95%. Results: A male prevalence of 50.7% was found in the study population, the mean age was 19 years, and 81% were in the late teens, 62% had a poor level of knowledge about sexual health and reproductive, 78% start sexual life with average age of 16 years, a large percentage of these students have between 1 and 3 sexual partners a year. Seventy percent used a condom at their first sexual intercourse and 12.3% of the population used the emergency pill. Conclusions: The level of knowledge about sexual and reproductive health is deficient. Most students surveyed use at least one method of family planning in their sexual relationships.